Deteksi Autisme pada Anak Menggunakan Metode Modified K-Nearest Neighbor (MKNN) - Zahra Swastika Putri; Rekyan Regasari Mardi Putri; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Autism is a childhood and developmental disorder that characterized by lack of communication, cognition, imagination and social interaction activities. Many people didn't recognize the symptoms of autism disorder until the first three or seven years of life. Delay, similarities of symptoms and lack of knowledge about autism cause imprecision treatment handling, and increased number of sufferers. Identification of autism differentiated into severe autism, moderate autism, mild autism and non- autism. Modified K-Nearest Neighbor (MKNN) method is a method that enhancing performance of conventional K-Nearest Neighbor method. There're validity of the train data process and weight voting process to robust neighbors of training dataset and strengthen the performance results. Based on variant value of k testing obtained 83.33% accuracy at dissimilarity measure. Based on composition of balance training data testing obtained 90% accuracy at euclidean distance. Based on amount of training data testing obtained 79.17% average accuracy. Based on variation of training data testing obtained 83.33% accuracy at dissimilarity measure. Based on results of such testing accuracy, pointed out that the detection of children's autism using MKNN method have a pretty good degree of accuracy and capable to classify and detection the autism symptoms based on perceived symptoms user input.